Market Knowledge: Evidence from Importers - Aksel Erbahar (Tinbergen Institute, 2017)
Previous firm-level literature established that there are substantial costs of entry into new export markets. Chaney (2014) opens the black-box of entry costs by building a dynamic network model of international trade where firms acquire customers in new destinations through their existing customers in other destinations. Following his conjecture, this paper examines whether firms use their existing suppliers in a destination to find their first clients in those markets. I use a disaggregated dataset on Turkish firms' exports and imports for the 2003-08 period, and investigate the effect and the channels that import experience might have on export entry. By identifying import experience using instrumental variables, and shutting down productivity channels with firm-year fixed effects, I find that having a supplier in the destination country raises the probability of exporting to that country by 5.5 percentage points on average, revealing a "market knowledge" phenomenon. The paper's main contribution to the literature is finding for the first time that firms' country-specific import experience increases the likelihood of exporting to that country. Digging further to explore heterogeneous effects, I find that this effect increases with the destination country's size, proximity, language similarity, and the size of its Turkish community. Moreover, the strength of the firm's relationship with its supplier as proxied by several variables such as the share of imported products that are differentiated increases the probability of export market entry.
Keywords: F1; F14; F61; L20; 330; market entry; export diversification; learning by importing; networks